Method for observing formation of nano-porous intermetallic compound by in-situ transmission electron microscope
The process of preparing nanoporous intermetallic compounds by observing the gas-phase dealloyment method through in-situ transmission electron microscopy solves the problem of incomplete understanding of this process in the prior art, and realizes in-depth observation and regulation of the nanoporous material formation mechanism.
Patent Information
- Application Number
- CN202411581922.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
AI Technical Summary
The existing process of preparing nanoporous intermetallic compounds by gas-phase dealloyment method has not been fully explored, especially the mechanisms of grain nucleation and ligament formation, which affect the regulation of material characteristics and ligament size.
The microscopic precursor alloy is prepared by focusing ion beam technology (FIB) using in-situ transmission electron microscopy (TEM) observation method, and high-temperature and low-pressure reaction is carried out on the in-situ heating TEM sample rod to observe the formation process of nanoporous intermetallic compounds in real time. .
Real-time observation of the dynamic process of preparing nanoporous intermetallic compounds in the gas-phase dealloy method is achieved, and key information on hole formation and ligament development is captured to help regulate the microstructure and performance of the material.
Smart Images

Figure CN119395052A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparing nanoporous materials by vapor phase dealloying, and in particular to a method for observing the formation of nanoporous intermetallic compounds by in-situ transmission electron microscope. Background Art
[0002] At present, the most commonly used method for preparing nanoporous intermetallic compounds is dealloying: electrochemical dealloying, liquid metal dealloying, and vapor phase dealloying. Electrochemical dealloying usually produces chemical waste, which is not only unfriendly to the environment, but also requires additional costs for waste treatment and recovery of dissolved elements. Liquid metal dealloying requires higher temperatures, especially chemical etching processes cannot be avoided to remove the solidified metal melt in the dealloying pores. In addition, only a limited number of elements can meet the miscibility requirements for the manufacture of nanoporous intermetallic compounds. Vapor phase dealloying refers to the process of selectively evaporating low evaporation components from alloys and diffusing and reorganizing high evaporation point components to form nanoporous structures under a certain temperature and vacuum degree by using the saturated vapor pressure difference of different metal elements. And the high temperature and low pressure reaction environment provided by vapor phase dealloying can well overcome the kinetic energy barrier required to form nanoporous intermetallic compounds.
[0003] The formation process of nanoporous intermetallic compounds prepared by vapor phase dealloying has not been well explored, including how grains nucleate and how ligaments are formed during the dealloying process. Therefore, understanding the formation process of nanoporous intermetallic compounds is crucial for regulating the ligament size and material properties of nanoporous intermetallic compounds.
[0004] In-situ transmission electron microscopy (TEM) characterization can be used to analyze the change of the internal structure of the material with temperature and obtain the physical law of the change of the material microstructure with the external environment. The in-situ heating TEM experiment is based on the in-situ heating chip. The sample is fixed to the chip by adjusting the angle and height of the FIB sample stage and thinned to a suitable thickness. After the sample is prepared, the chip is placed on the matching in-situ TEM sample rod with heating function, and then the in-situ heating TEM characterization experiment is carried out. Summary of the invention
[0005] In order to more intuitively analyze the process of preparing nanoporous intermetallic compounds by vapor phase dealloying, the purpose of the present invention is to provide a method for in situ observation of the formation of nanoporous intermetallic compounds during vapor phase dealloying, which is not only suitable for in situ TEM testing in high temperature environments, but also can realize high-resolution TEM in situ observation.
[0006] To achieve the above object, the technical solution of the present invention is: A method for in-situ transmission electron microscopy observation of the formation of nanoporous intermetallic compounds, the method comprising the following steps: S1: Prepare microscopic precursor alloys using focused ion beam technology (FIB) and transfer them to the TEM in-situ heating chip. Take the grains of the precursor alloy as the research object and process them using focused ion beam technology (FIB). After selecting a suitable sample area, depositing a protective layer, preliminary cutting, sample extraction and transfer, secondary thinning and fine-tuning of the sample, and cleaning of the amorphous layer on the sample surface, a chip sample is obtained. The process of sample extraction and transfer is as follows: first, the angle of the sample stage is adjusted to an ideal extraction angle, which corresponds to an ideal placement angle for placing the sample on the in-situ heating chip. The setting of the ideal placement angle can ensure that the angle between the thin slice sample and the chip is within 15°; Insert the Easylift needle to the other side where the sample is connected to the matrix, insert the Pt needle for welding, then withdraw the Pt needle, cut the part where the target sample is connected to the matrix and lift the sample into the chamber, then adjust the sample stage to make the in-situ heating chip at the ideal placement angle. At the ideal placement angle, the in-situ heating chip is within the tilting range of the β angle of the in-situ TEM sample rod, so that the sample is placed as parallel to the in-situ heating chip as possible, and finally insert the Easylift needle to place the target sample; Then insert the Pt needle and weld the sample on the in-situ heating chip by welding on both sides; S2: The chip sample of S1 is mounted on a matching in-situ TEM sample holder, and then placed in a transmission electron microscope for real-time observation; S3: heating and keeping the sample warm to observe the formation process of the nanoporous intermetallic compound; S4: Use morphological characterization, energy spectrum analysis and selected area electron diffraction analysis on samples at different temperatures to analyze the microscopic information of the reaction process.
[0007] Furthermore, the selection of a suitable sample area includes: finding a suitable sample area under the conditions of 2 kV and 0.1 nA in the electron beam window, and adjusting the height and angle of the sample stage so that the sample area under the electron beam window and the ion beam window is co-focused at one point; Depositing the protective layer: Preheat and insert a Pt needle, first deposit a 200-300nm protective layer under the electron beam window at 2kV and 0.4-0.8nA to prevent irradiation damage under the ion beam window, and then continue to deposit a 1-2μm protective layer under the ion beam window at 30kV and 72pA-0.23nA; The preliminary cutting is as follows: firstly, the Pt needle is withdrawn, and then pits are dug out on both sides of the protective layer at the ion beam window to expose the target sample, and a "U-shaped" rectangular frame is used to interrupt the four sides of the target sample so that only one side is connected to the parent sample; The secondary thinning and fine-tuning of the sample: performing secondary thinning on the sample fixed on the in-situ heating chip under the conditions of ion beam window 30 kV, 2.5 nA, and sample stage (17±1°), gradually reducing the beam current and thinning width until the ideal thickness is achieved; The cleaning of the amorphous surface of the sample: first remove the protective layer using 5kV and 15-41pA under the ion beam window, and then use 2kV and 9pA to sweep the amorphous layer on the surface of the sample at a large angle.
[0008] Furthermore, the precursor alloy is suitable for any sample that can be used to prepare nanoporous materials by gas phase dealloying, including a binary copper-zinc system, a binary magnesium-nickel system, and the like.
[0009] The transmission sample of S1 after FIB processing needs to avoid interference from the amorphous layer and retain the vacuum part.
[0010] The transmission electron microscope used in the S2 is a transmission electron microscope with condenser spherical aberration corrected.
[0011] The method for forming the nanoporous intermetallic compound used in S3 is a vapor phase dealloying method.
[0012] The precursor alloy is a magnesium-nickel binary alloy, and the process of obtaining the chip sample in S1 is: The first step is to select a suitable sample area: find a suitable sample area under the electron beam window conditions of 2kV and 0.1nA, adjust the sample stage height and angle to 3.92mm and 52°, so that the sample area under the electron beam window and the ion beam window is cofocused at one point; The second step is to deposit a protective layer: select a Pt needle for preheating and inserting, first deposit a Pt protective layer of 8μm in length, 1.5μm in width, and 200~300nm in thickness under the conditions of 2kV, 0.4~0.8nA, and 0° on the sample stage under the electron beam window to prevent irradiation damage under the ion beam window, and then continue to deposit a protective layer of about 1-2μm under the conditions of 30kV, 72pA~0.23nA, and 52° on the sample stage under the ion beam window; The third step is preliminary cutting: first withdraw the Pt needle, then dig pits on both sides of the protective layer under the conditions of 30kV, 6.5nA and 52° of the ion beam window, and then use a small beam current of 30kV and 2.5nA to fine-tune the target sample under the conditions of the sample stage (52±1°) to expose a smooth target sample. After rotating the sample stage to 0°, use a "U-shaped" rectangular frame under the conditions of 30kV and 2.5nA of the ion beam window to cut and interrupt the four sides of the target sample, so that only one side is connected to the parent sample; The fourth step is sample extraction and transfer: first adjust the angle of the sample stage to 58°, insert the Easylift needle to the other side where the sample is connected to the mother body, insert the Pt needle for welding, then withdraw the Pt needle, cut the part where the target sample is connected to the mother body and take the sample out of the chamber, then stick the in-situ heating chip on the 45° stage of the sample stage to break the film at the window of the heating chip to retain the vacuum part, rotate the sample stage horizontally 180° and adjust the height and angle of the sample stage to 3.92mm and 23°, so that the sample is placed as parallel to the in-situ heating chip as possible, finally insert the Easylift needle to place the target sample and insert the Pt needle to weld the sample to the in-situ heating chip by welding on both sides; The fifth step is secondary thinning and sample refinement: thin the sample fixed on the in-situ heating chip under the conditions of ion beam window 30kV, 2.5nA, and sample stage (17±1°), and gradually reduce the beam current and thinning width to perform cyclic thinning on the sample until the ideal thickness is achieved; The sixth step is to clean the amorphous layer on the sample surface: remove the protective layer under the conditions of 5kV, 15~41pA, and sample stage (17±1°) in the ion beam window, and then clean the amorphous layer on the sample surface under the conditions of 2kV, 9pA, and sample stage (17±3°); The S1 chip sample was mounted on a matching in-situ TEM sample rod and then placed in a transmission electron microscope for real-time observation. The sample was heated and kept warm to observe the formation process of the nanoporous intermetallic compound. The reaction temperature was 450°C and the reaction time was 60s-300s.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The prior art uses non-in-situ TEM to illustrate the evolution of gas-phase dealloying, using samples from the same batch but under different conditions (temperature, time) to enter the electron microscope for observation. Because the material is put into the electron microscope for static observation after the experimental operation, it is impossible to capture the dynamic information of the material during the actual reaction and change process, and a lot of important information may be missed. Therefore, this application uses in-situ TEM technology to fill this gap, and can observe the dynamic process of preparing nanoporous intermetallic compounds by gas-phase dealloying in real time under different reaction conditions. For example: the conditions for the appearance of holes and the dynamic process of ligament formation, etc.
[0014] The present invention adopts a two-side welding method when extracting and transferring samples to reduce the expansion effect caused by temperature phase changes. Combined with in-situ TEM, the evolution process of samples with component loss during gas phase dealloying can be observed in situ, which makes up for the shortcomings of in-situ observation in the study of gas phase dealloying to prepare intermetallic compounds.
[0015] When transferring samples, the method of the present invention transfers the samples to the window of the horizontally placed heating chip instead of vertical placement as in conventional techniques, so that the angle between the transferred samples and the horizontally placed heating chip is sufficiently small.
[0016] The method of the present invention for observing the formation of nanoporous intermetallic compounds by in-situ transmission electron microscopy (TEM) is to heat a heating chip to a certain temperature and keep the temperature in a TEM environment, so as to observe the formation process of nanoporous intermetallic compounds generated by a vapor phase dealloying method. The observation method of the present invention is to observe the formation process of nanoporous intermetallic compounds under in-situ conditions, and can realize high-temperature, high-stability and high-resolution in-situ TEM observation, which is easy to operate and has excellent observation effect, and is of great value in promoting and expanding the research and application of nanoporous metal materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the Mg-Ni binary alloy phase diagram of Example 1; Figure 2 This is a TEM cross-sectional view of the Mg2Ni precursor alloy material prepared by using a focused ion beam-electron beam dual beam device in Example 1; Figure 3 TEM images of the ligament formation process of the non-porous Mg2Ni precursor alloy transforming into a nanoporous intermetallic compound at different temperatures observed in Example 1; (a)-(f) are TEM images at different temperatures during the gas phase dealloying process; Figure 4 This is an energy spectrum analysis diagram of the gas phase dealloying phase transformation process observed in Example 1; Figure 5 This is a high-angle annular dark field image of the Mg2Ni phase at room temperature (25°C) in Example 1; Figure 6 is the selected area electron diffraction pattern of the Mg2Ni phase at room temperature (25°C) in Example 1; Figure 7 This is a high-angle annular dark field image of the nanoporous MgNi2 intermetallic compound prepared by the vapor phase dealloying method in Example 1; Figure 8 is a selected area electron diffraction pattern of the nanoporous MgNi2 intermetallic compound prepared by the vapor phase dealloying method in Example 1; Fig. 9 Schematic diagram of the sample stage tilt angle change process during sample extraction and transfer and secondary thinning in Example 1; Fig.10 This is a comparison diagram of the FIB sample cutting products of Example 1 and Comparative Example 1; DETAILED DESCRIPTION
[0018] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It is particularly noted that the specific embodiments described herein are only used to explain the relevant inventions, rather than to limit the present invention.
[0019] See also Figure 1-9 , a method for in-situ transmission electron microscopy observation of nanoporous intermetallic compound formation, the method comprising the following steps: S1: Microscopic precursor alloy is prepared using focused ion beam technology (FIB) and transferred to the TEM in-situ heating chip.
[0020] The first step is to select a suitable sample area: find a suitable sample area under the electron beam window conditions of 2kV and 0.1nA, adjust the sample stage height and angle to 3.92mm and 52°, so that the sample area under the electron beam window and the ion beam window is cofocused at one point; The second step is to deposit a protective layer: select a Pt needle for preheating and inserting, first deposit a Pt protective layer of 8μm in length, 1.5μm in width, and 200~300nm in thickness under the conditions of 2kV, 0.4~0.8nA, and 0° on the sample stage under the electron beam window to prevent irradiation damage under the ion beam window, and then continue to deposit a protective layer of about 1-2μm under the conditions of 30kV, 72pA~0.23nA, and 52° on the sample stage under the ion beam window; The third step is preliminary cutting: first withdraw the Pt needle, then dig pits on both sides of the protective layer under the conditions of 30kV, 6.5nA and 52° of the ion beam window, and then use a small beam current of 30kV and 2.5nA to fine-tune the target sample under the conditions of the sample stage (52±1°) to expose a smooth target sample. After rotating the sample stage to 0°, use a "U-shaped" rectangular frame under the conditions of 30kV and 2.5nA of the ion beam window to cut and interrupt the four sides of the target sample, so that only one side is connected to the parent sample; The fourth step is sample extraction and transfer: first adjust the angle of the sample stage to 58° (this angle corresponds to the angle of the in-situ heating chip, and the ideal angle is 58°), insert the Easylift needle to the other side where the sample is connected to the mother body, insert the Pt needle for welding, then withdraw the Pt needle, cut the part connected to the mother body of the target sample and lift the sample into the chamber, then stick the in-situ heating chip on the 45° stage of the sample stage to break the film at the chip window to retain the vacuum part, rotate the sample stage horizontally 180° and adjust the height and angle of the sample stage to 3.92mm and 23° (see Fig. 9c) (the ideal placement angle should take into account the tilting range of the β angle of the in-situ TEM sample rod. In this embodiment, the tilting range is ±15°. At this time, the ideal placement angle of the sample stage is 23°, so that the angle between the thin slice sample and the heating chip is 10°. At this angle, the atomic image can be observed during the reaction process). Place the sample as parallel to the in-situ heating chip as possible. Finally, insert the Easylift needle to place the target sample and insert the Pt needle to weld the sample to the in-situ heating chip. When the sample is welded to the in-situ heating chip, the two side edges of the opposite surfaces of the sample and the heating chip are connected together by welding on both sides. Welding on both sides achieves the stability of the sample during the reaction process while considering the cost. In the embodiment of the present application, due to the evaporation of Mg during the heating process, the sample has a large stress and the sample as a whole will have a violent expansion. Welding on both sides can effectively offset the expansion, so that the sample tends to be in a stable state during the heating process, and can also make the system heated evenly without the problem of crystal band axis deflection, thereby ensuring the stability of the phase change process.
[0021] Fig. 9 In the initial stage, the sample stage and the sample are kept vertical, and the angle between the sample stage and the horizontal plane is 0° (see Fig. 9 In this initial state, adjust the sample stage angle to the ideal angle of 58°. At this time, the angle between the sample and the horizontal plane is 32°, and the sample stage and the sample remain vertical (see Fig. 9 Then, the heating chip is attached to the 45° stage of the sample stage to break the vacuum portion of the film at the chip window. After the sample stage is rotated 180° horizontally, the angle between the sample stage and the horizontal plane is 23°, and the angle between the sample and the heating chip is 10° (see Fig. 9 (c) in the figure), in this state, the welding operation between the sample and the heating chip can be carried out.
[0022] The fifth step is to thin the sample again and refine the sample: thin the sample fixed on the in-situ heating chip under the conditions of 30 kV, 2.5 nA and sample stage (17 ± 1°) in the ion beam window (see Fig. 9 (d) in the figure), and gradually reduce the beam current and the thinning width to cyclically thin the sample until the ideal thickness is about 100nm.
[0023] The sixth step is to clean the amorphous layer on the sample surface: remove the protective layer under the conditions of 5kV, 15~41pA and sample stage (17±1°) in the ion beam window, and then clean the amorphous layers on the upper and lower surfaces of the sample under the conditions of 2kV, 9pA and sample stage (17±3°).
[0024] S2: The chip sample of S1 is mounted on the corresponding in-situ TEM sample holder, and then placed in a transmission electron microscope for observation in real time; S3: heating and keeping the sample warm to observe the formation process of the nanoporous intermetallic compound; S4: Use morphological characterization, energy spectrum analysis and selected area electron diffraction analysis on samples at different temperatures to analyze the microscopic information of the reaction process.
[0025] In the method of the present invention, the sample is applicable to any sample that can be used to prepare nanoporous materials by gas phase dealloying, such as the preparation of nanoporous intermetallic compounds from a binary copper-zinc system.
[0026] Among them, the transmission sample of S1 after FIB processing needs to avoid interference from the amorphous layer and retain the vacuum part.
[0027] Among them, the transmission electron microscope used by S2 is a condenser spherical aberration corrected transmission electron microscope.
[0028] Among them, the method used in S3 to form the nanoporous intermetallic compound is a vapor phase dealloying method.
[0029] Example 1 Embodiment 1 of the present invention provides an in-situ observation method for the formation of a magnesium-nickel nanoporous intermetallic compound, which specifically comprises the following steps: (1) The smooth surface (small grains) of the Mg2Ni precursor alloy prepared by arc melting and strip spinning was selected as the research object, and it was processed using the focused ion beam technology (FIB), which went through the following processes: selecting a suitable sample area, depositing a protective layer, preliminary cutting, sample extraction and transfer, secondary thinning and sample finishing, and cleaning the amorphous layer on the sample surface. The final Mg2Ni TEM thin section specimen (block structure with a length of about 8μm and a width of about 4μm) has a thickness of about 100nm and a grain size of about 200nm, see Figure 2 .
[0030] The sample extraction and transfer process is as follows: first adjust the angle of the sample stage to 58° (this angle corresponds to the angle of the sample stage when it is placed on the in-situ heating chip), insert the Easylift needle to the other side where the sample is connected to the matrix, insert the Pt needle for welding, then withdraw the Pt needle, cut the part where the target sample is connected to the matrix and take the sample out of the chamber, then stick the in-situ heating chip on the 45° stage of the sample stage to break the thin film at the chip window to retain the vacuum part, rotate the sample stage horizontally 180° and adjust the sample stage height and angle to 3.92mm and 23° (this angle should take into account the tilting range of the in-situ TEM sample rod β angle, which is ±15° in this embodiment, At this time, the angle between the sample and the chip is 10°), so that the sample is placed as parallel to the in-situ heating chip as possible, and finally, the Easylift needle is inserted to place the target sample and the Pt needle is inserted to weld the sample on the in-situ heating chip, and the two side edges of the sample opposite to the heating chip are connected together by welding on both sides. The welding on both sides realizes the stability of the sample during the reaction process under the premise of considering the cost. In the embodiment of the present application, due to the evaporation of Mg during the heating process, the sample as a whole will have a violent expansion. The welding on both sides can effectively offset the expansion, so that the sample is always in a stable state during the heating process, and the system can also be heated evenly without the problem of crystal band axis deflection, thereby ensuring the stability of the phase change process.
[0031] (2) The Mg2Ni TEM thin section sample was placed in a condenser spherical aberration corrected transmission electron microscope for observation. According to the difference in saturated vapor pressure of Mg and Ni elements under different temperature conditions, and according to Figure 1 From the Mg-Ni binary alloy phase diagram shown, it can be seen that the transformation from Mg2Ni phase to porous MgNi2 phase is a gradual phase change process, so nanoporous MgNi2 intermetallic compounds are prepared by the gas phase dealloying method.
[0032] (3) Use the in-situ heating system to heat and keep the sample on the heating chip warm.
[0033] (4) Characterization and analysis Figure 3 This is a series of in-situ STEM images of the in-situ observation of the process of preparing nanoporous MgNi2 intermetallic compounds by vapor phase dealloying during the heating process of the Mg2Ni precursor alloy in Example 1 of the present invention. Figure 3 (a) is the morphology of Mg2Ni precursor alloy at room temperature. Figure 3 (b)-(f) is 450℃(1.0×10 -5 A series of morphological diagrams of nanoporous MgNi2 intermetallic compounds formed by gas phase dealloying under constant temperature conditions (MPa vacuum environment). Figure 3It can be seen that small holes appear at 450℃, and then observed at a constant temperature of 450℃, it is found that the holes gradually expand, and at the same time as the holes expand, nanoporous metal ligaments are formed, which gradually spread over time to form a bicontinuous nanoporous structure. The ligament size of the nanoporous structure formed at a constant temperature of 450℃ is about 30nm. Figure 4 The energy spectrum analysis diagram analyzed the non-porous area and the porous structure area respectively, and it was found that the non-porous area was still Mg2Ni phase, and the porous structure area formed was MgNi2 phase.
[0034] Then through the Figure 5 The HAADF-STEM image of the Mg2Ni phase was analyzed to determine that the Mg2Ni phase axis is the
[100] axis, and Figure 6 Selected area electron diffraction analysis found that the (001) direction period in Mg2Ni was destroyed, which was manifested as the elongation of the (001) and (002) diffraction points; and at the intercalation position where the periodicity was destroyed, there was slip between the (001) direction crystal planes, resulting in a slip distance of about 1 / 3 of that of the (010) plane. Figure 7 (a) is the low-power morphology of the porous MgNi2 intermetallic compound. Figure 7 (b) is Figure 7 (a) The enlarged image of the yellow box. Figure 8 Selected area electron diffraction further confirmed that the phase was MgNi2 phase.
[0035] Comparative Example 1 This comparative example adopts a single-side welding method based on Example 1. The effect comparison between the two is shown in FIG. Fig.10 ; Example 1 adopts bilateral welding. Compared with the comparative example, the overall sample of bilateral welding is more stable during the heating process, can offset the influence of thermal expansion well, has smaller axial deflection, and can observe the atomic image well.
[0036] The method of the present invention observes the formation process of nanoporous intermetallic compounds under in-situ conditions, can realize high-temperature, high-stability and high-resolution in-situ TEM observation, is easy to operate, and has excellent observation effect. It is of great value in promoting and expanding the research and application of nanoporous metal materials.
[0037] Matters not described in the present invention are applicable to the prior art description.
Claims
1. A method for in-situ transmission electron microscopy observation of the formation of nanoporous intermetallic compounds, characterized in that: The method comprises the following steps: S1: Prepare a microscopic precursor alloy using focused ion beam technology and transfer it to a TEM in-situ heating chip. Take the grains of the precursor alloy as the research object and process them using focused ion beam technology. After selecting a suitable sample area, depositing a protective layer, preliminary cutting, sample extraction and transfer, secondary thinning and fine-tuning of the sample, and cleaning of the amorphous layer on the sample surface, a chip sample is obtained; The process of sample extraction and transfer is as follows: first, the angle of the sample stage is adjusted to an ideal extraction angle, which corresponds to an ideal placement angle for placing the sample on the in-situ heating chip. The setting of the ideal placement angle can ensure that the angle between the thin slice sample and the chip is within 15°; Insert the Easylift needle to the other side where the sample is connected to the matrix, insert the Pt needle for welding, then withdraw the Pt needle, cut the part where the target sample is connected to the matrix and lift the sample into the chamber, then adjust the sample stage to make the in-situ heating chip at the ideal placement angle. At the ideal placement angle, the in-situ heating chip is within the tilting range of the β angle of the in-situ TEM sample rod, so that the sample is placed as parallel to the in-situ heating chip as possible, and finally insert the Easylift needle to place the target sample; Then insert the Pt needle and weld the sample on the in-situ heating chip by welding on both sides; S2: The chip sample of S1 is mounted on a matching in-situ TEM sample holder, and then placed in a transmission electron microscope for real-time observation; S3: heating and keeping the sample warm to observe the formation process of the nanoporous intermetallic compound; S4: Use morphological characterization, energy spectrum analysis and selected area electron diffraction analysis on samples at different temperatures to analyze the microscopic information of the reaction process.
2. The method for in-situ transmission electron microscopy observation of nanoporous intermetallic compound formation according to claim 1, characterized in that: The selecting of a suitable sample area comprises: finding a suitable sample area under the conditions of 2 kV and 0.1 nA in the electron beam window, and adjusting the height and angle of the sample stage so that the sample area under the electron beam window and the ion beam window is co-focused at one point; Depositing the protective layer: Preheat and insert a Pt needle, first deposit a 200-300nm protective layer under the electron beam window at 2kV and 0.4-0.8nA to prevent irradiation damage under the ion beam window, and then continue to deposit a 1-2μm protective layer under the ion beam window at 30kV and 72pA-0.23nA; The preliminary cutting is as follows: first withdraw the Pt needle, then dig pits on both sides of the protective layer in the ion beam window to expose the target sample, and use a "U-shaped" rectangular frame to interrupt the four sides of the target sample so that only one side is connected to the mother sample; The secondary thinning and fine-tuning of the sample: performing secondary thinning on the sample fixed on the in-situ heating chip under the conditions of ion beam window 30 kV, 2.5 nA, and sample stage (17±1°), gradually reducing the beam current and thinning width until the ideal thickness is achieved; The cleaning of the amorphous surface of the sample: first remove the protective layer using 5kV and 15-41pA under the ion beam window, and then use 2kV and 9pA to sweep the amorphous layer on the surface of the sample at a large angle.
3. The method for in-situ transmission electron microscopy observation of nanoporous intermetallic compound formation according to claim 1, characterized in that: The precursor alloy is suitable for any sample that can be used to prepare nanoporous materials by gas phase dealloying, including a binary copper-zinc system and a binary magnesium-nickel system.
4. The method for in-situ transmission electron microscopy observation of nanoporous intermetallic compound formation according to claim 1, characterized in that: The transmission sample of S1 after FIB processing needs to avoid interference from the amorphous layer and retain the vacuum part.
5. The method for in-situ transmission electron microscopy observation of nanoporous intermetallic compound formation according to claim 1, characterized in that: The transmission electron microscope used in the S2 is a transmission electron microscope with condenser spherical aberration corrected.
6. The method for in-situ transmission electron microscopy observation of nanoporous intermetallic compound formation according to claim 1, characterized in that: The method for forming the nanoporous intermetallic compound used in S3 is a vapor phase dealloying method.
7. The method for in-situ transmission electron microscopy observation of nanoporous intermetallic compound formation according to claim 1, characterized in that: The precursor alloy is a magnesium-nickel binary alloy, and the process of obtaining the chip sample in S1 is: The first step is to select a suitable sample area: find a suitable sample area under the electron beam window conditions of 2kV and 0.1nA, adjust the sample stage height and angle to 3.92mm and 52°, so that the sample area under the electron beam window and the ion beam window is cofocused at one point; The second step is to deposit a protective layer: select a Pt needle for preheating and inserting, first deposit a Pt protective layer of 8μm in length, 1.5μm in width, and 200~300nm in thickness under the conditions of 2kV, 0.4~0.8nA, and 0° on the sample stage under the electron beam window to prevent irradiation damage under the ion beam window, and then continue to deposit a protective layer of about 1-2μm under the conditions of 30kV, 72pA~0.23nA, and 52° on the sample stage under the ion beam window; The third step is preliminary cutting: first withdraw the Pt needle, then dig pits on both sides of the protective layer under the conditions of 30kV, 6.5nA and 52° of the ion beam window, and then use a small beam current of 30kV and 2.5nA to fine-tune the target sample under the conditions of the sample stage (52±1°) to expose a smooth target sample. After rotating the sample stage to 0°, use a "U-shaped" rectangular frame under the conditions of 30kV and 2.5nA of the ion beam window to cut and interrupt the four sides of the target sample, so that only one side is connected to the parent sample; The fourth step is sample extraction and transfer: first adjust the angle of the sample stage to 58°, insert the Easylift needle to the other side where the sample is connected to the mother body, insert the Pt needle for welding, then withdraw the Pt needle, cut the part where the target sample is connected to the mother body and take the sample out of the chamber, then stick the in-situ heating chip on the 45° stage of the sample stage to break the film at the window of the heating chip to retain the vacuum part, rotate the sample stage horizontally 180° and adjust the height and angle of the sample stage to 3.92mm and 23°, so that the sample is placed as parallel to the in-situ heating chip as possible, finally insert the Easylift needle to place the target sample and insert the Pt needle to weld the sample to the in-situ heating chip by welding on both sides; The fifth step is secondary thinning and sample refinement: thin the sample fixed on the in-situ heating chip under the conditions of ion beam window 30kV, 2.5nA, and sample stage (17±1°), and gradually reduce the beam current and thinning width to perform cyclic thinning on the sample until the ideal thickness is achieved; The sixth step is to clean the amorphous layer on the sample surface: remove the protective layer under the conditions of 5kV, 15~41pA, and sample stage (17±1°) in the ion beam window, and then clean the amorphous layer on the sample surface under the conditions of 2kV, 9pA, and sample stage (17±3°); The S1 chip sample was mounted on a matching in-situ TEM sample rod and then placed in a transmission electron microscope for real-time observation. The sample was heated and kept warm to observe the formation process of the nanoporous intermetallic compound. The reaction temperature was 450°C and the reaction time was 60s-300s.